Rethinking dynamic equivalence as a rhetorical construct. Issue 2 (3rd May 2020) - Robinson, Douglas
ABSTRACT: Eugene Nida's concept "dynamic equivalence" is well-known all over the world – or is it? In this paper I argue first that Nida himself didn't understand the implications of his concept very well, and later, in shifting to the term "functional equivalence, " ruined it completely; then that it is effectively a rhetorical concept, in which the equivalence sought is not between two functions but between two rhetorical situations. To develop this, the paper folds Nida's concept into Aristotle's three channels of persuasion, logos (logical persuasion), ethos (authoritative persuasion), and pathos (emotional persuasion), and explores the implications for Nida's own work in Bible translation; and then tackles problems faced in translating another sacred text, namely the Chinese Mengzi . Interwoven with these arguments are reports of classroom discussions on them with a class of Chinese MA students in Hong Kong.